Oxidative Stress in Assisted Reproductive Techniques, with a Focus on an Underestimated Risk Factor - Mauchart, Péter; Vass, Réka Anna; Nagy, Bernadett; Sulyok, Endre; Bódis, József; Kovács, Kálmán (Current Issues in Molecular Biology, 2023)
Based on current findings, the presence of oxidative stress has a significant impact on the quality of gametes and embryos when performing assisted reproductive techniques (ART). Unfortunately, in vitro manipulation of these cells exposes them to a higher level of reactive oxygen species (ROS). The primary goal of this review is to provide a comprehensive overview of the development of oxidative stress in female and male reproductive systems, as well as in the case of the pre-implantation embryo and its environment. This review also focuses on the origins of ROS and the mechanisms of oxidative stress-induced damage during ART procedures. A well-known but underestimated hazard, light exposure-related photo-oxidation, is particularly concerning. The effect of oxidative stress on ART outcomes, as well as the various strategies for preventing it, are also discussed. We emphasize the role and significance of antioxidants and light protection including forms, functions, and mechanisms in the development of gametes and embryos in vivo and in vitro.